The multiple inert gas elimination technique (MIGET) - Hopkins, Susan R.; Wagner, P. D. (Springer, 2017)
This is the first book to bring together the history, theory, mathematical approach, measurement details and limitations of the Multiple Inert Gas Elimination Technique (MIGET) and a summary of the global literature on its application in health and disease over the last 40 years. Up to the early 1970's, and despite substantial research carried out by leaders in respiratory physiology, it was not possible to measure the most important and most complex component of gas exchange in the lung: ventilation/perfusion (VA/Q) heterogeneity. Building on that earlier research, MIGET was developed to overcome this large gap in our understanding of the most important function of the lung. Just as CT and MRI make use of multiple, simultaneous imaging views to reconstruct the underlying anatomy spatially, MIGET uses the simultaneous exchange of six inert gases with differing blood solubility to reconstruct the functional distribution of VA/Q ratios. While the basic physiological principle of MIGET is straightforward, using inert gas exchange data to construct the VA/Q distribution requires complicated mathematics along with the ability to simultaneously measure the exchange of six foreign gases present in just parts per million or less. This unique book is a valuable resource for anyone interested in how the lung works.- Resumé vydavatel
Keywords: plíce; dýchání; fyziologie člověka; lungs; respiration; human physiology; elektronické knihy; monografie; electronic books; monographs